Academic stress level guidance and counseling students at Universitas Negeri Padang - Neviyarni, Neviyarni; Andriani, Irna; Ahmad, Riska (Universitas Negeri Padang, 2018)
The phenomenon found in the field when students are given assignments, they will complain a lot. Counseling technique course I is a course that has many lectures.This article aims to describe academic stress level of students of Guidance and Counseling who are taking Counseling Technique Course I. It is seen from the emotional, intellectual, physical, and interpersonal symptoms. The study used a descriptive quantitative approach with the subject of 104 students. Data were collected using an academic stress scale. The results of the study reveal the level of academic stress of the students of the Guidance and Counseling Department who are taking the subjects of Counseling Technique I viewed from: (1) emotional symptoms (2) intellectual symptoms (3) physical symptoms, and (4) interpersonal symptoms are in the medium category. Of the 17 existing academic stress indicators, only one indicator is in the low category. The results of this study are important to provide input for students, lecturers in Counseling Technique I, and academic counselor in order to help reduce student academic stress level.